Two-dimensional position-dependent massive particles in the presence of magnetic fields - Dutra, Alvaro de Souza [UNESP]; Oliveira, J. A. de [UNESP] (Iop Publishing Ltd, 2009)
In this work, we discuss the problem of a particle with a position-dependent mass interacting with a two-dimensional potential well with finite depth, as well as under the influence of a uniform magnetic field. The ordering ambiguity is taken in account, and we obtain the exact wavefunctions and energies for a complete set of eigenstates. It is shown that, even considering a finite-depth potential well, the system retains an infinite set of quantum states.